1981
DOI: 10.1210/jcem-52-3-508
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoreactive Somatomedin Levels in Normal Adults, Pregnant Women at Term, Children at Various Ages, and Children with Constitutionally Delayed Growth*

Abstract: Immunoreactive somatomedin (IRSM) levels in term pregnancy material sera (MS) and newborn cord sera (CS) were higher and lower, respectively, than those in normal adults. IRSM levels in MS and CS were not correlated, suggesting that SM dose not cross the placenta. The similar levels of IRSM in arterial and venous CS suggest that the placenta does not produce SM. IRSM levels in CS were higher than those in newborn sera and were correlated with day 1 newborn sera, suggesting that the placenta may regulate fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
64
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(77 citation statements)
references
References 29 publications
12
64
1
Order By: Relevance
“…The pattern obtained in this study was similar to the pubertal IGF-I surge reported in humans and rats [14,15], although this was not clear in previous studies of Meishan boars [16,17]. Such a change has not been reported in E u r o p e a n b r e e d s , s o t h i s c h a n g e m a y b e characteristic of Meishan pigs.…”
Section: Discussionsupporting
confidence: 79%
“…The pattern obtained in this study was similar to the pubertal IGF-I surge reported in humans and rats [14,15], although this was not clear in previous studies of Meishan boars [16,17]. Such a change has not been reported in E u r o p e a n b r e e d s , s o t h i s c h a n g e m a y b e characteristic of Meishan pigs.…”
Section: Discussionsupporting
confidence: 79%
“…The preferential induction of adrenocortical androgen secretion by IGFs is probably based on their predominant and direct stimulation of the 17 -hydroxylase/17,20-lyase (P450c17) expression, which is a key enzyme of androgen biosynthesis (L'Allemand et al 1996, Kristiansen et al 1997. Since the onset of adrenarche is characterized by a relative increase in P450c17 activity and coincides with an increase in IGF-I serum levels (Bala et al 1981), it is tempting to speculate that the IGF system may be involved in the developmental regulation of adrenal androgen secretion. Furthermore, activation of the IGF-I receptor by IGFs or high levels of circulating insulin has been implicated in the pathogenesis of various states of hyperandrogenemia such as polycystic ovary syndrome (Barbieri et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of IGF-I development from childhood to adult life has been more consistently established (8,12,26). Although the methodologies are still evolving, the plasma IGF-I concentration typically increases with age in young children (>10.3 nM or 80 /Lg/L) with a prominent surge (>51 nM or 400 /LgIL) at puberty (20,27).…”
Section: Discussion Table 4 Correlation Of Individual Concentrationsmentioning
confidence: 99%
“…Although the methodologies are still evolving, the plasma IGF-I concentration typically increases with age in young children (>10.3 nM or 80 /Lg/L) with a prominent surge (>51 nM or 400 /LgIL) at puberty (20,27). Thereafter, plasma IGF-I declines steadily until normal adult values are reached (12,25). After 40 y of age, IGF-I declines again to levels lower than in early adulthood (26).…”
Section: Discussion Table 4 Correlation Of Individual Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation